(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the methods and technology of processing Goji fruit, as well as its economic efficiency, which describes the products used in industry to make compotes, jams and jams from Goji fruit, their quantity and technology. The useful properties and chemical composition of the finished product are also described